The Pulmonary Embolism Response Team: What Is the Ideal Model? - Rodriguez-Lopez, Josanna; Channick, Richard (Seminars in Respiratory and Critical Care Medicine, 2017)
Treatment of patients with intermediate- and high-risk pulmonary embolism (PE) is a controversial area. Many therapeutic options exist, and deciding on appropriate treatment can be difficult. In addition, multiple specialties are often involved in the care of PE patients. To better organize the response to serious PE patients, several hospitals and academic centers across the United States, spearheaded by Massachusetts General Hospital, have created pulmonary embolism response teams (PERTs). The goal of a PERT is to have a single multidisciplinary team of experts in thromboembolic disease, who can respond rapidly to patients with acute PE, and offer consultation with the full spectrum of therapeutic options. PERT teams were modeled after rapid response teams and are meant to generate a prompt, patient-specific plan for patients with PE without having to consult multiple individual specialists.
Keywords: pulmonary embolism; rapid response teams; team-based approach; venous thromboembolism